1995
DOI: 10.1111/j.1600-0714.1995.tb01196.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53 protein in oral squamous cell carcinomas and adjacent non‐tumorous mucosa of the floor of the mouth: an archival immunohistochemical study using wet autoclave pretreatment for antigen retrieval

Abstract: Routinely formalin-fixed and paraffin-embedded material of 22 squamous cell carcinomas of the floor of the mouth (T2NoMo, Ro), together with adjacent dysplastic or normal mucosa, were immunohistochemically investigated using a panel of four anti-p53 antibodies (CM1, PAb1801, DO7, PAb240) subsequent to wet autoclave pretreatment for antigen retrieval. p53 immunoreactivity was detected in 9/22 (40%) carcinomas with PAb1801 and DO7 antibodies, and in 8/22 cases using CM1 and PAb 240. p53-positive tumour cells acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 24 publications
1
11
1
3
Order By: Relevance
“…This might also indicate a normally working p53 system activated in genetically stressed cells that could either be restored or pushed towards apoptosis or enter the vicious circle of malignant transformation. [16] In OSCC cases, including both the study groups, we found that 31 out of total 60 cases (51.67%) showed positive expression for p53 protein by IHC analysis. Our findings were in agreement with Kurokawa, who performed a study to evaluate a potential association between the histological grade of malignancy at the deep invasive front and the expression of Ki-67 antigen and p53 protein in OSCC patients and found p53 immunoexpression in 54% of tumours.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This might also indicate a normally working p53 system activated in genetically stressed cells that could either be restored or pushed towards apoptosis or enter the vicious circle of malignant transformation. [16] In OSCC cases, including both the study groups, we found that 31 out of total 60 cases (51.67%) showed positive expression for p53 protein by IHC analysis. Our findings were in agreement with Kurokawa, who performed a study to evaluate a potential association between the histological grade of malignancy at the deep invasive front and the expression of Ki-67 antigen and p53 protein in OSCC patients and found p53 immunoexpression in 54% of tumours.…”
Section: Discussionmentioning
confidence: 95%
“…It was consistent with the studies of Langdon, Partridge (1992), Rich et al (1999), Nylander et al (2000), and with most other reports in the literature, regardless of differences in antibodies, IHC procedures, and types of specimens (frozen or paraffin-embedded sections) used. [20][21][22][23][24][25] On the contrary, the normal oral mucosa was found to be p53 positive by Piffko et al (1995), but this was tissue adjacent to malignant epithelium that might represent an early event in oral carcinogenesis. This might also indicate a normally working p53 system activated in genetically stressed cells that could either be restored or pushed towards apoptosis or enter the vicious circle of malignant transformation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, some studies (Kropveld et al, 1999 andBalz et al, 2003) have shown that the analysis of the entire coding region of TP53 (exons 2-11) in head and neck SCC increases the frequency of mutations and yields a greater concordance level with immunohistochemistry results, although many caveats may lead to false-positive or false-negative results (Piffkó et al, 1995;Dowell & Ogden, 1996;McNicol & Richmond, 1998;Stoll et al, 1998;Saunders et al, 1999;Nylander et al and Gonzalez-Moles et al).…”
Section: P53 Immunoexpression In Oral Squamous Cell Carcinomas From Dmentioning
confidence: 99%